Сотрудничество учёных НТУ "Харьковский политехнический институт" и ученых России в области науки и техники - Бесов, Л. М.; Гутник, Марина Валерьевна; Лисачук, Георгий Викторович (НТУ "ХПИ", 2007)
В статье освещаются вопросы сотрудничества ученых НТУ "Харьковский политехнический институт" с учеными из России. Материал излагается в хронологическом порядке и содержит информацию о выдающихся ученых в области физики, химии, механики, оказавших влияние на развитие мировой науки и техники. Приводятся данные о сотрудничестве в области исследования космоса, технологий машиностроения. Делается заключение о промахах в социально-гуманитарной сфере.

Paper illustrates questions concerning with collaboration between scientists of NTU "Kharkov polytechnic university" and scientists from Russia. The material is stated in chronological order and the information about prominent scientists in area of physics, chemistry, mechanics which had action upon evolution of science and technique of the world is contained. The data about collaboration in the field of space, technologies of machine-building investigation are given. The conclusion about misses in socially-humanitarian area is made
Keywords: НТУ "ХПИ"; ученые; научно-педагогическая работа